Risk factors for perihilar cholangiocarcinoma: A hospital‐based case–control study. (7th July 2014) - Lee, Ban Seok; Cha, Byung Hyo; Park, Eun‐Cheol; Roh, Jaehoon
Abstract Background & Aims Perihilar cholangiocarcinoma (pCCA) is the most common form of bile duct cancer, arising from cholangiocytes at the confluence of hepatic ducts. Given the diversity of cholangiocarcinoma (CCA) aetiology according to the location, and the scarcity of studies on the aetiology of pCCA, we aimed to identify the risk factors for pCCA. Methods A total of 81 patients diagnosed with pCCA between July 2007 and December 2013, and 162 controls matched 2:1 for age, sex and date of diagnosis were included in this hospital‐based case–control study. Potential risk factors were retrospectively investigated through clinical records, and the associations with pCCA were studied by calculating the odds ratios (ORs) using conditional logistic regression analysis. Results In the univariate model, the prevalence of choledocholithiasis (OR: 14.00, P = 0.014), hepatolithiasis (OR: 12.00, P = 0.021) and diabetes mellitus (DM) (OR: 2.74, P = 0.005) was higher in pCCA patients than in controls. Heavy smoking and cirrhosis were marginally significant risk factors for pCCA (P < 0.1). Multivariate analysis revealed an association between pCCA and hepatolithiasis, choledocholithiasis, DM, and heavy smoking, each, with adjusted ORs of 16.47, 9.39, 3.36 and 2.52 respectively. DM, heavy smoking, hepatolithiasis and choledocholithiasis accounted for about 22.5%, 17.1%, 8.5% and 4.8% of pCCA risk respectively (population attributable risk percentage). Conclusion Our data showed that DM, heavy smoking, choledocholithiasis and hepatolithiasis were risk factors for pCCA development, implying that pCCA may share some aetiological factors with intrahepatic CCA although it has been classified as extrahepatic CCA.